In memoriam: Marco Frascari (1945-2013) - Jenner, Ross (Interstices: Journal of Architecture and Related Arts, 2013)
(link here to DREAMHOUSE ARCHITECTURE, a website linking professionals and students interested in Marco Frascari’s work)